(3GdEbJUGO GdSjGSj ddJfejI aj GdbQfjf GdYTQjf hGdhGMO hGdYTQjf (B/s - (3Gejf, SejQs ((3HjQhJ(B: s (3OGQ GdaGQGHj(B, s, 2002)
(3jOhQ eMhQ gPg GdOQGSI Mhd GdGbJUGO GdSjGSj ddJfejI aj GdbQfjf GdYTQjf hGdhGMO hGdYTQjf(B. (3gPG hEf GdCacGQ GdJj jbJQMgG GdHGMK aj OQGSJg JJfGhd (B\"(3eTcdGJ GdJfejI(B\" (3ceG jLH Cf JWQM YfO eWdY GdbQf GdhGMO hGdYTQjf hjbhd GdHGMK HCf bQGAI GdfXQjGJ hGdeeGQSGJ GdJj JMceJ HeYGdLI gPg GdeTcdGJ NdGd GdfUa GdKGfj ef GdbQf GdYTQjf, dG JgOa EdqG Edi GdeSGYOI aj JTNjU WHjYI GdJMOjGJ GdJj JhGLg GdYGde, ajeG jJYOi GdeBRb GdJj WHYJ, HfXQ GdHGMK, XQha fgGjI gPG GdbQf, aGbJVi GdJTNjU efg EHQGR eG JMedg gPg GdeTcdGJ ef LOjO, hGdOQhS GdJj jecf GSJNdGUgG ef JLQHI GdbQf GdYTQjf(B. (3hJQJcR JMdjdGJg Ydi fXQjI aj GdQCSeGdjI haj HYOgG GdYGdej, hHUhQI CTed fXQjI aj OjfGejI GdJMhd GdGLJeGYj, eSJfOkG aj Pdc Ydi CWQhMGJ eQcRjI KdGK dhVY GdbGQF aj GdLqh GdPj jSJWjY ef NdGdg age eVehf GdOQGSI(B. (3gPg GdCWQhMGJ JJfGhd eQcRjI GdGSJdGH GdGbJUGOj GdPj jeqjR GdQCSeGdjI hjJHGjf aj Bmf eYkG eY eG cGfJ Ydjg GdeLJeYGJ GdSGHbI heG jecf Cf jchfg eLJeY eG HYO GdQCSeGdjI eQcRjI GdGSJbWGH GdfGLe Yf YhdeI GdQCSeGdjI eQcRjI eG SeGg GdHGMK (B\"(3HGdJMOjO GdefNaV(B\" (3aj GdJGQjN(B. (3gPg GdCWQhMGJ GdKdGK eLJeYI bGOJ GdHGMK HUhQI WHjYjI Edi GdGSJfJGL HCf (B\"(3bVjI GdJfejI(B\" (3JMJd ehbYkG eQcRjkG aj GdeLJeY GdeYGUQ, hCfgG de JLO MdkG HYO, hdG jecf dgPG GdMqd Cf jfJL aj EWGQ GdQCSeGdjI(B. (3hgcPG aEf eaghe GdJfejI PGJg gh eaghe fbOj(B. (3hbO GNJGQ GdHGMK efgLjI dHMKg JLdJ aj YQV GdYfGUQ GdJj HOJ dg bWYkG CSGSjI aj GdQbYI GdeYbOI GdJj JTcdgG bQGAGJ GdJGQjN GdeJYdbI HgPG GdehVhY, hJMdjdGJ GdGSJQGJjLjGJ GdJj JMJd GdeSQM GdeYGUQ, hEHQGR GdCWQhMGJ GdfXQjI hGdCjOjhdhLjI GdehVhYI aj MqjR GdaYd(B. (3gPG hEf JhdjO gPg GdYfGUQ aj GdQbYI jSeM HEYGOI JQcjH GdeTGgO GdeMJedI Ydi GNJdGagG ddeSJbHd GdPj jfHfj, hJbjje bOQJgG GdfSHjI aj GdELGHI Ydi JMOj GdJWhQs
Keywords: (3GdGbJUGO GdSjGSjs; (3GdJfejI GdGbJUGOjIs; (3JfejIs